Solving for 'a' in the Equation (a + b/c)(d) = f
This article will guide you through the steps to solve for 'a' in the equation (a + b/c)(d) = f.
Understanding the Equation
The equation represents a scenario where you are multiplying a sum of two terms by a constant 'd', and the result is equal to 'f'. Our goal is to isolate 'a' on one side of the equation.
StepbyStep Solution

Distribute: Start by distributing the 'd' across the terms inside the parentheses:
ad + (b/c)d = f

Simplify: Combine the terms with 'd':
ad + bd/c = f

Isolate 'ad': Subtract 'bd/c' from both sides of the equation:
ad = f  bd/c

Solve for 'a': Finally, divide both sides of the equation by 'd' to isolate 'a':
a = (f  bd/c) / d
Simplifying the Solution
You can further simplify the solution by finding a common denominator for the terms in the numerator:
a = (cf  bd) / cd
Final Result
The solution for 'a' in the equation (a + b/c)(d) = f is:
a = (cf  bd) / cd
Key Points to Remember
 This solution assumes that 'c' and 'd' are nonzero values. If either 'c' or 'd' is zero, the equation becomes undefined.
 You can apply this method to solve for any variable in similar equations. Just remember to isolate the variable you want to solve for by using algebraic operations.